Semantische Technologien im Entwurf mechatronischer Systeme: Effektiver Austausch von Lösungswissen in Branchenwertschöpfungsketten - Gausemeier, Jürgen; Trächtler, Ansgar; Schäfer, Wilhelm; Anacker, Harald; Bauer, Frank; Borcherding, Holger; Dziwok, Stefan; Frank, Ursula; Herden, Rudolf; Hoppe, Gerd; Just, Viktor; Kiele-Dunsche, Markus; et al.
Cooperative cyber-physical systems (CCPS) are driven by the tight coordination between computational components, physical sensors and actuators, and the interaction with each other over system bounds. The software development of CCPS is getting more complex because of the tight integration, heterogeneous technologies, as well as safety and timing requirements. Therefore, new engineering approaches, such as model-driven development methods, are required, along with communication architectures with self-* capabilities. Both will support the developer in specifying such a system effectively and efficiently. However, the application of such techniques to the development of CCPS has not been addressed sufficiently so far. This paper presents an experience report of developing a cooperative delta-robot system that juggles a ball without a central control or camera system. For the development, an intelligent network architecture and model-driven development method for CCPS are applied.

Discursive business model development - Successful positioning in the competitive arena through integrative development of market performance and business { \ "a} ftsmodell - Gausemeier, J {\ "u} rgen; Amshoff, Benjamin (ZWF magazine for ü r economic factory operation)

Approach for Scenario-Based Test Specifications for Virtual Commissioning - Schneider, Marcel; Gausemeier, Jürgen; Schmuedderich, Tanja; Trächtler, Ansgar (Proceedings of the DESIGN 2014 - 13th INTERNATIONAL DESIGN CONFERENCE)

Selbstoptimierung verteilter mechatronischer Systeme auf Basis paretooptimaler Systemkonfigurationen - Münch, Eckehard

Acceleration of Material Flow Simulations - Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Ein Beitrag zur Verhaltensantizipation und -regelung kognitiver mechatronischer Systeme bei langfristiger Planung und Ausführung - Hartmann, P.

Vorausschau und Technologieplanung. 10. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 20. und 21. November 2014 - Gausemeier, Jürgen

Ändern sich die beruflichen Anforderungen an Masterabsolventen und Doktoranden der Wirtschaftsinformatik? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Herausforderungen und Chancen eines Wechsels zwischen Hochschulsystemen - Eymann, T.; Kundisch, Dennis; Recker, J.

Computer und Internet im Spiegel migrationsspezifischer Disparitäten - Vennemann, Mario; Gerick, Julia; Eickelmann, Birgit (Grundschule in der digitalen Gesellschaft. Befunde aus den Schulleistungsstudien IGLU und TIMSS 2011)